The Pengaruh Motivasi Dan Gaya Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran TIK - Cipto Anugrah (CV. DIGITIAL EDUKASI NUSANTARA, 2025)
This study looks at how learning motivation and learning styles affect the results students get in the ICT subject for tenth graders at SMK Setih Setio 2 Muara Bungo. The background says there are differences in how well students do, and this is thought to be because of different levels of motivation and learning styles. The study uses ideas about motivation, types of learning styles like visual, auditory, and kinesthetic, and what shows learning outcomes. The research method is causal correlation. The group studied is all tenth-grade students, and they were chosen using total sampling. The tools used were a questionnaire for motivation, a questionnaire for learning styles, and a test for learning results. All of these were checked to make sure they work well and give accurate results. The data was then analyzed using multiple linear regression with SPSS. The study found that learning motivation has a positive and important effect on how well students do (tcount is bigger than ttable and sig is less than 0.05). Learning styles also have a strong one (tcount is smaller than ttable and sig is bigger than 0.05). When both are considered together, they both have a significant effect on learning results (Fcount is bigger than Ftable and sig is less than 0.05). So, motivation is the main factor that influences academic success, while learning styles work better with the help of teachers.